RELAŢIA PROFESOR–ELEV, RELAŢIE DE SIMPATIE ŞI EMPATIE - USM ADMIN (Studia Universitatis Moldaviae: Stiinte ale Educatiei, 2007)
For the education of the new generation the teachers must put into value their whole professional skill and capacity, aiming at building up the proper framework needed to shorten the distance between them and those whom they should share with the national and universal values. Such inter-personal relationship is based upon the mutual capacity of understanding, anticipation, and identification of partners (teacher and student), in order to be able of mutual trust needed for this purpose and opens the way to empathic communication between the educator and the educated person. Basically, we consider important emphasizing from the very beginning that the investigation of the skills and vocation for instructive and educational activities (for which the sympathetic and empathic capacities play the role of guiding entity) are justified as necessity for achieving the progress of the entire educational process. It is hard to imagine the educational process developed without teachers able to create the proper educational atmosphere, establish efficient relationships with the students, and to build up the framework for communication, which can influence this process.